Who lives in the Arctic? - Canizares, Susan, 1960-; Chanko, Pamela, 1968- (New York : Scholastic, 1998)
Photographs and simple text explore the variety of animals that have adapted to life in the Arctic.
1.2
K-3
Keywords: Zoology -- Arctic regions -- Juvenile literature; Zoology -- Arctic regions; Zoology; Arctic regions -- Juvenile literature; Arctic regions; Arctic regions